HUBUNGAN TINGKAT PENGETAHUAN PENGHUNI KOS TENTANG HIV/AIDS TERHADAP KESEHATAN REPRODUKSI DI DUSUN GLENDONGAN, TAMBAK BAYAN, CATUR TUNGGAL, DEPOK, SLEMAN, YOGYAKARTA - Nova Nusa Indah; Patria Asda; Heni Febriani (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2015)
ABSTRACTBackground: Of the five counties and municipalities in Yogyakarta, Yogyakarta city was ranked first with HIV/AIDS. In Yogyakarta there are 423 people living with HIV and there are 210 people living with AIDS. The second rank was occupied by the Sleman district with 279  234 people living with HIV and AIDS. Bantul district ranks third with 249 189 people living with HIV and people living with AIDS. Progo district was rated four with 62 people living with HIV and 46 people with AIDS. Gunungkidul be at least the district HIV/AIDS. There are 40 people with HIV and 65 people with AIDS in Gunungkidul. The purpose of this study was to determine the relationship of the level of knowledge about the disease boarders of HIV/AIDS on reproductive health in the hamlet Glendongan, Tambakbayan, Caturtunggal, Depok, Sleman, Yogyakarta.Objective: to know relationship boarders level of knowledge about HIV/AIDS in the hamlet Glendongan Tambakbayan Caturtunggal Depok Sleman Yogyakarta.Methods: This study is a quantitative research study design using cross sectional method. Population and samples in this study were student boarders in the village Glendongan, and collecting data using questionnaires instrument. Statistical analysis using Chi-square test with a significance level of 0.05%.Results: Knowledge of HIV/AIDS 82.5% and 85% reproductive health, this suggests that there is a relationship between the boarders of knowledge about HIV/AIDS and reproductive health, where the results obtained are: P-value = 0.000 ≤ α = 0, 05.Conclusion: There is a significant relationship between the level of knowledge about HIV/AIDS to reproductive health by boarders